PENGARUH PENERAPAN TEKNIK KANCING GEMERINCING DENGAN PENGGUNAAN HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 SITIUNG DHARMASRAYA - Shalvia, Ana; ZA, Nilawasti; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
The research is motivated by a discussion that was dominated by a group of highly capable students and students lack of understanding of mathematical concepts. This can be seen in the results of learning mathematics class VIII student SMP 1 Sitiung Dharmasraya school year 2012/2013. This study aims to determine whether students understanding of mathematical concepts by applying Kancing Gemerincing techniques with using handouts better than the students understanding of mathematical concepts by applying conventional learning. This type of research is experimental, with the design of randomized on the subject. The results of the data analysis is known that the two samples are normally distributed and homogeneous on the real level of 0.05. Hypothesis test results obtained P-value is 0.000. The result is less than Î± of 0.05, then the hypothesis in this research received. It can be concluded that the students understanding of mathematical concepts by applying techniques Kancing Gemerincing with using handouts better than the students understanding of mathematical concepts by applying conventional learning in class VIII student SMP 1 Sitiung Dharmasraya.